Transitive RNA silencing signals induce cytosine methylation of a transgenic but not an endogenous target. (6th May 2013) - Vermeersch, Leen; De, Nancy; Nolf, Jonah; Bleys, Annick; Kovařík, Aleš; Depicker, Ann
Summary Post‐transcriptional gene silencing of a primary target gene in plants can coincide with the production of secondary small interfering RNAs (siRNAs) of coding sequences adjacent to the target region and with de novo RNA‐directed DNA methylation (RdDM) thereof. Here, we analyzed the susceptibility of transgenic and endogenous targets to RdDM induced by primary and secondary silencing signals. In three different configurations, primary silencing signals were able to direct in trans methylation of chimeric transgenes and the CATALASE2 (CAT2) endogene; however, extensive spreading of methylation occurred only in the transgene, resulting in the methylation of the flanking CAT2 sequence, whereas methylation of the CAT2 endogene was restricted to the target region and the enclosed introns. The secondary silencing signals arising from this transgenic primary target simultaneously silenced a secondary transgene target and the CAT2 endogene, but were only capable of directing RdDM to the transgene. Our data indicate that RdDM is correlated with the in situ generation of secondary siRNAs, occurring in P35S‐driven transgenes but not in most endogenes. We conclude that although both endogenes and transgenes are equally sensitive to transitive silencing, differences exist in their susceptibility to undergo secondary RdDM.